STUDI PEMIKIRAN AL-MAQASHID (Upaya Menemukan Fondasi Ijtihad Akademik yang Dinamis) - Mth, Asmuni (Islamic University of Indonesia, 2005)
The goal of Shariah ( ilm al-maqashid ) historically develop dynamically. This science shows free and sporadic earlier. Then, it develops evolutively and it becomes one of basic of established Islamic law thought. The goal of tashri can be classified into three categories, al-masalih ad-daruriyah, al-haji, and al-tahsini. This classification does not answer law problerms academically. Because of ilm al-maqasid is not only departing from linguistics understanding toward Quran and Sunnah, but also considers the values deriving from society. especially moral norms. So, al-masalih that relates to and as reference of the academic intellectual exercise is al-masalih al-hayawiyah, al-masalih al-aqliyah, and al-masalih ruhiyah. This classification will comprehend Islamic law integratively all of maslahah, it implies that Islamic law will be applicable and functionable to solve society problem.